DIFFERENTIATED TREATMENT OF ISOLATED TRAUMATIC INJURY OF FRONTAL LOBES OF THE BRAIN - M. M. Smirnova; Yu. A. Shcherbuk; S. A. Morozov (Вестник хирургии имени И.И. Грекова, 2018)
An analysis of treatment results was made in 83 patients with traumatic parenchymatous injuries of frontal lobes of the brain. Surgical interventions were performed in 31 patients and the conservative therapy was carried out in 52 patients. Regular neurological examinations were completed for all the patients. The data of neurovisual methods were estimated. A strategy of treatment of frontal lobes injury depends on not only from the traumatic substratum volume, but at the same time, it is formed by clinical neurologic constellations and instrumental data in traumatic injury of frontal lobes of the brain. Risk factors of unfavorable effect of traumatic parenchymatous injury of frontal lobes of the brain were reflected in the initially low GCS score, a neurologic deficit progression with contusion haemorrhagic foci in the frontal lobe (volume greater than 25 cm³), a midline shift on 6 mm or more and signs of base cistern compression and presence of mass-effect, according to CT scan data. The developed algorithm could improve the results of treatment and makes better the quality of life of the patients with traumatic parenchymatous injuries of frontal lobes of the brain.